2010
DOI: 10.1177/147470491000800312
|View full text |Cite
|
Sign up to set email alerts
|

Altruism between Romantic Partners: Biological Offspring as a Genetic Bridge between Altruist and Recipient

Abstract: When the cost of altruism is low, individuals are more likely to help non-kin (i.e., friends and romantic partners) than kin. This trend is thought to reflect the fact that people tend to be emotionally closer with friends and romantic partners than kin. However, as the cost of altruism increases, altruistic preference shifts to kin. The present study highlights this phenomenon by examining altruism between siblings, romantic partners, romantic partners who have biological children together, and romantic partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This is the first time in the literature that gender differences in altruism between romantic partners and relatives in a sample of young adults are so consistently, extensively, and precisely reported. Previous research either did not find any gender differences among participants (Stewart-Williams, 2008; Fitzgerald et al, 2010), just found them in middle-aged and older samples (Neyer & Lang, 2003), or for a single relative type, namely offspring (Hernández Blasi & Mondéjar, 2018). The results are consistent with, on the one hand, an evolutionary perspective that emphasizes variables like the degree of genetic relatedness and the reproductive value to understand altruistic behavior, as well as the role of women as “kin-keepers” (Hames, 2015) and with, on the other hand, psychology and economics theorizing and evidence suggesting that men and women behave, feel and think differently with respect to helping behavior (Eagly & Crowley, 1986; Falk & Hermle, 2018; Gilligan, 1982).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This is the first time in the literature that gender differences in altruism between romantic partners and relatives in a sample of young adults are so consistently, extensively, and precisely reported. Previous research either did not find any gender differences among participants (Stewart-Williams, 2008; Fitzgerald et al, 2010), just found them in middle-aged and older samples (Neyer & Lang, 2003), or for a single relative type, namely offspring (Hernández Blasi & Mondéjar, 2018). The results are consistent with, on the one hand, an evolutionary perspective that emphasizes variables like the degree of genetic relatedness and the reproductive value to understand altruistic behavior, as well as the role of women as “kin-keepers” (Hames, 2015) and with, on the other hand, psychology and economics theorizing and evidence suggesting that men and women behave, feel and think differently with respect to helping behavior (Eagly & Crowley, 1986; Falk & Hermle, 2018; Gilligan, 1982).…”
Section: Discussionmentioning
confidence: 84%
“…Finally, we believe it would be interesting to provide some complementary information about romantic partners and relatives in the questionnaire, such as relatives' gender, and the number children of a romantic partner and relatives. As previous research work has demonstrated (Fitzgerald et al, 2010), the participants' decision making might change in hypothetical life-or-death situations in accordance with romantic partners having children or not. It might also be wise to increase the hypothetical age of older romantic partners: most 25-year-old romantic partners have a higher reproductive value than 40year-old ones, but the reproductive value of a 40-year-old women and a 40-year-old man are not likely equivalents.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…instance, Stewart-Williams (2007) classified helping behaviours as either low (e.g., emotional support), medium (e.g., help during illness, providing financial support) or high cost (e.g., donating a kidney). Fitzgerald, Thompson, and Whitaker (2010) attempted to measure helping behaviour directed towards kin and non-kin based on cost of helping. To assess high-cost helping, participants were asked how willing they would be to donate a kidney to their kin or to save them from a burning building.…”
mentioning
confidence: 99%